Recent progress on the development of herbal medicine in Malaysia - Khatib, Alfi (2015)
Standardization of medicinal herbs is one of Malaysian government strategy to warranty the quality of these herbs. One novel approach in standardization of the medicinal herbs is metabolomics. Metabolomics is a comprehensive analysis of the whole metabolites in a sample. Identification of both chemical and bio-markers can be performed by the instrumental analysis of both natural sources and animal biofluids and multivariate data analysis. All advanced instrumentation such as nuclear magnetic resonance spectroscopy, liquid chromatography-mass spectrometry, and gas chromatography-mass spectrometry are used in metabolomics. In this presentation, we give some examples of the application of metabolomics approach to identify the bioactive compounds in Orthosipon stamineus, Cosmos caudatus, and Melicope ptelefolia. This approach is also able to predict the bioactivity of these herbs. As a conclusion: metabolomics open the possibility to fasten the identification of novel bio- and chemical markers, and the validated calibration model can be used to predict the bioactivity of new set of herbal extract.